Caracterização e utilização de subprodutos do mamão (Carica papaya L.) - Santos, Cláudia Mendes dos (2015)
The processing of the fruit results in large quantities of waste and thus new aspects on the use of this waste as by-products with paper food additives has aroused great interest. Papaya is one of the most important tropical fruits currently grown in the country and the world. Being only the pulp of the papaya consumed, and the rest of the fruit, peel and seeds, it is rejected. These byproducts can serve as elements for alternative uses and their studies, based on the chemical characteristics. Thus, this work was carried out aiming to chemically characterize the flour from the bark and fruit seed obtained from two papaya cultivars (Hawaii and Calimosa) in relation to the nutrients, antinutrients and antioxidant capacity, and prepare loaves added whole way such meal. They determined the proximal mineral composition, the content of sugars, vitamin C, carotenoids, phenolics and antioxidant capacity of the flour. The form of whole loaves prepared with the addition of 0, 3, 6 and 9% of a mixed meal (skin and seeds) were characterized chemically and sensorially. The flour papaya peel showed higher levels than the flour seed in the parameters: fiber, ash, phenolic compounds, vitamin C, soluble solids, titratable acidity, and minerals copper, sulfur and potassium. Since the contents in the seed meal was higher than in the shell flour, protein, lipids, and minerals, calcium, iron, magnesium and zinc. The addition of mixed flour promoted an increase in the levels of total protein and dietary fiber, and decreased lipid levels in breads elaborate way. The integrally bread with added 3% mixed flour obtained a good acceptance despite the decrease in technological quality. The addition of flour and papaya seed hulls in the preparation of bakery products adds value to these products, reduces environmental pollution and prevents its release to the environment.